Narratives of border reinforcement: The role of knowledge and communications power - Sergio Peña (Estudios Fronterizos, 2019)
The general objective of this paper is to analyze and explain the paradox of why objective knowledge based upon “facts and hard data” has been insufficient to forge a narrative, particularly in the U.S. side, that would lead towards a deeper cooperation and make the U.S.-Mexico border more fluid, functional and integrated. The main question is:  why the “re-territorialization” narrative of reinforcing differences and solidifying the border has prevailed? The theoretical framework that guides this analysis is the Aristotelian concept of “phronesis” or “practical wisdom” to settle beliefs that cannot be reached through an objective scientific rationality. The issue of power is of great interest in this analysis; particularly, the paper explores the relationship between knowledge and communications power as explanatory factors to understand the forging of a narrative of reinforcing borders. The conclusion is that the military-surveillance industrial complex has been the most influential actor behind the kind of knowledge that shape border policy compared to academic and scientific knowledge.